Functional analysis of the determinant of the formation of green infrastructure of urban environment in a historical retrospective according to the stages of improvement and transformation (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The analysis of the functions of green infrastructure elements in a historical retrospective makes it possible to outline the further path of development of the architectural and urban planning formation of green infrastructure of the urban environment and in further research to make an objective assessment of which methods and techniques will have a positive impact not only on the environment, but also correlate with the cultural, aesthetic values of society. The article carries out a functional analysis of the methods of landscaping settlements, the development of garden and park art at the conditional stages of Improvement and Transformation of green infrastructure of the urban environment, which correspond to the industrial and post-industrial historical eras. Functional analysis through the prism of historical retrospective in combination with a systemic approach made it possible to identify determinants that influence the development of green infrastructure of the present day and outline the vector of the path of further development of the formation of green infrastructure of the urban environment as an ecological system. As a result of the study, it was found that the functions of green infrastructure elements are transformed together with the transformation of the green infrastructure system and are scaled. Thus, green infrastructure elements, combining into subsystems and systems, integrated with the urban planning system and the city's transport system, perform such functions as: ecological, social, historical and cultural, economic, urban planning. The author concluded that given the fact that at the stage of the Transformation of the Green Infrastructure of the urban environment there is a shift in emphasis to street networks, along with which there is a change in the functions of the structural element of the special-purpose territory itself, such as: service streets and parking lots are transformed into landscape and recreational linear parks. However, such a transformation of the structural elements of the urban environment not only indicates the fact of changing the protective function of street landscaping to a complex of functions, including, in particular, aesthetic, recreational, engineering-recreational and environmental functions, but also provides a solution to the problem of congestion, floods and heat islands in the urban environment.The further path and development trends of the formation of green infrastructure of the urban environment, as an ecological system, are outlined as a concept of combining the principles of forming green infrastructure of the urban environment with the preservation of structural elements of the urban environment but with a change in the functional purpose of the latter, using techniques and methods of transformation, renovation and revitalization.
Keywords: green infrastructure; functions of green infrastructure; transformation of urban environment; transformation of green infrastructure of cities; systemic approach; elements of green infrastructure